Assessment of Hospitality education in terms of Lacking Skill Development in Meeting the demand of Industry: An Integrative review - Kumar, Pradip; Chansoria, Mukesh (Revista de turism - studii și cercetări în turism, 2021)
The hospitality and tourism industry is one of the key drivers to contribute to the Indian economy. It has continuously excelled in other industries in terms of both generating GDP and Employment (Center for Economic Policy Research ). According to IBEF (India Brand Equity Foundation) Indian tourism is rich in variety, it has natural, heritage, medical, religious, and cultural tourism in its account. In FY20 it has created 39 million jobs which is 8% of total employment in India. It is expected to reach 52.3 million jobs by 2028. India has ranked 10th worldwide in the tourism sector according to WTTC and it has contributed Rs.13,68,100 crore which is 6.8% of the Indian economy. Indian hospitality education and industry both have been developing tremendously but there is a significant gap between the skills demand of industry and supply by academia. The study is an integrative review of previous research and it establishes the gap and provides suggestions to bridge this gap. Study has some limitations as the previous studies taken are from different countries not not only from India. The study will help various stakeholders to revisit their technologies and methodologies to mitigate this skill gap.